(untitled) (Eurasian Journal of Philology Science and Education, 2018)
The article deals with the structure of the onmics of the Turkic historical written monuments. When the membership of the composition of proper names is determined, the predominance of two-parted onms is revealed, which are linked by agreement in Turkic onomastics by reviewing the history of classification by composition. The methods of formation of the onmy monuments «Divani Hikmet», «Gift of Truth», «Mukhabbat-name» and «Kutadgu bilig» are investigated. It is revealed that approximation as a method of secondary name is created on the basis of a structural description of similarities. In the monuments there are onyms created by merging the bases, i.e. in the process of contamination. In the anthroponyms of Aitoldy, Kuntudy of the work «Kutadgu bilig», the components of Ai, Kun are subject, and the component of the crowd is the predicate. In different linguistic situations, the change of anonym or one of its elements (phonemes, morphemes, lexemes), i.e. Onim are considered, which have arisen on the basis of the allonim. Identified such types of allonyms as: official and unofficial, literary and dialectal, literary and regional, stylish, transcript, chronological. The onyms, formed by epenthesis, are found. Used in oral speech, formed on the basis of borrowed words, where the features of the native language are taken into account.